Chemical looping reforming of toluene as a biomass tar model compound over two types of oxygen carriers: 2CuO-2NiO/Al2O3 and CaFe2O4. (15th June 2018) - Wang, Zhiqi; Zhu, Min; He, Tao; Zhang, Jinzhi; Wu, Jingli; Tian, Hanjing; Wu, Jinhu
Highlights: Chemical looping reforming of biomass-based toluene was firstly reported. Two reduced oxygen carriers can further catalyze the cracking of toluene. Unique 2CuO-2NiO/Al2 O3 oxygen carrier completely combust toluene to CO2 . CaFe2 O4 partially oxidize toluene to CO and H2 with a high reactivity. Toluene can be fully converted by two oxygen carriers. Abstract: Chemical looping reforming/gasification of toluene, the model compound representing biomass tar, was studied by using two oxygen carriers, 2CuO-2NiO/Al2 O3 (molar ratio) and CaFe2 O4 . Their reaction performances were evaluated in a TG-FTIR and a laboratory-scale fixed bed reactor. The active lattice oxygen of the 2CuO-2NiO/Al2 O3 oxygen carrier demonstrated excellent reactivity and completely oxidized toluene to CO2 at 600–700 °C, while the fixed bed reactor data indicated that 2CuO-2NiO/Al2 O3 oxygen carrier could catalyze the cracking of toluene to produce H2 after loss of lattice oxygen. The CaFe2 O4 oxygen carrier exhibited a good performance of chemical looping partial oxidation of toluene to CO and H2 with a fairly high reactivity. Over CaFe2 O4 oxygen carrier, the CO and H2 dominated reaction products in the temperature range of 800–900 °C except at the startup stage. Catalytic cracking of toluene by CaFe2 O4 to produce H2 was also observed after partial loss of lattice oxygen. Stable performance of CaFe2 O4 with high reactivity to syngas (CO and H2 ) was demonstrated during a 3-cyle test in the fixed bed reactor. After reduction of action with toluene, scanning electron microscopy (SEM) and X-ray diffraction (XRD) indicated that 2CuO-2NiO/Al2 O3 was reduced to metallic copper and nickel with the mixture of NiAl2 O4, and CaFe2 O4 was reduced to metallic iron and CaO. In summary, two oxygen carriers displayed high toluene conversion at the beginning stage and the conversion of toluene increased to about 100% in the subsequent stage.